A new approach for the analysis of Organophosphorus Isecticides from water using capillary electrophoretic techniques - Wan Ibrahim, Wan Aini (Faculty of Science, 2002)
The purpose of this study is to separate hydrophobic and hydrophilic OPPs using micellar electrokinetic chromatography (MEKC) with on-column UV detection and the challenge of decreasing the detection limit was met by online preconcentration methods. Successful separation of hydrophobic OPPs (methidathion, diazinon, quinalphos, chlorpyrifos and profenofos) was achieved by NM-MEKCSDS that comprised a separation buffer of 10 mM phosphate-borate (pH 9.3), 10 mM SDS and 10 % v/v 1:1 mixture of methanol-acetonitrile, where sample was prepared in similar buffer matrix and was injected by electrokinetic mode. Using online sample pre-concentration technique called sweeping (sweeping-NM-MEKC-SDS), sensitivity enhancement factors either in terms of peak areas (SEFarea) or in terms of peak heights (SEFheight) were found to be more than 10 for each pesticide. In reverse migration MEKC (RM-MEKC-SDS) with highly acidic separation buffer, only three OPPs viz. methidathion, quinalphos and either diazinon, profenofos or chlorpyrifos were resolved, as possible optimization scheme were unable to resolve the co-elution of diazinon, profenofos and chlorpyrifos. LODs in sub-ppm ranges were found attainable in sweeping-NM-MEKC-SDS. Hydrophilic OPPs (phosphamidon, dicrotophos and monocrotophos) were successfully separated in both basic and acidic phosphate buffer. A 100-fold improvement in detector response was achieved by stacking in reverse migrating micelles (SRMM) that corroborated the LODs in subppm level.